2011
DOI: 10.1902/jop.2010.100274
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Obesity: A Study of the Fourth Korean National Health and Nutrition Examination Survey

Abstract: A high WC seems to be associated with periodontitis, whereas BMI does not. This finding shows that abdominal obesity is significantly correlated with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 21 publications
9
69
1
4
Order By: Relevance
“…Men in particular are affected by variations in the amount of muscle and weight of bone (Dalla Vecchia et al, 2005), so that overweight BMI values are not necessarily indicative of excessive fat. Several cross-sectional studies concluded that WC or waist-tohip ratio was as strongly or more strongly related to odds of periodontal disease than BMI (Al-Zahrani et al, 2003;Wood et al, 2003;Kim et al, 2010). Using more than one index of obesity may refine the level of periodontitis risk.…”
Section: Discussionmentioning
confidence: 99%
“…Men in particular are affected by variations in the amount of muscle and weight of bone (Dalla Vecchia et al, 2005), so that overweight BMI values are not necessarily indicative of excessive fat. Several cross-sectional studies concluded that WC or waist-tohip ratio was as strongly or more strongly related to odds of periodontal disease than BMI (Al-Zahrani et al, 2003;Wood et al, 2003;Kim et al, 2010). Using more than one index of obesity may refine the level of periodontitis risk.…”
Section: Discussionmentioning
confidence: 99%
“…A probing force of ~20 g was used. Trained and calibrated dentists examined the periodontal status of the participants, and the mean inter-examiner Kappa value was 089 [95% confidence interval (CI), 0.55-1.00] (15,(22)(23).…”
Section: Socioeconomic Variablesmentioning
confidence: 99%
“…The results also show the association between PD and abdominal obesity along with: poor oral hygiene and smoking, with a high level of significance (p=0.001 and p=0.036, respectively). Chopra et al, Han et al and Kim et al adjusted the analysis to: monthly family income, alcoholism, physical activity, presence of active caries, number of decayed and lost teeth 20,22,31 . This is despite the fact that they determined the presence of oral hygiene indirectly using a questionnaire to find about the habits of brushing, flossing and an interproximal tooth- brush.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the effect of hypertension, dyslipidemia 31 and type 2 diabetes mellitus has been recognized as a risk factor for the PD, either individually or through the metabolic syndrome (MS Within the limitations of the study is the difficulty to operationally define abdominal obesity due to the fact that there is no consensus in the cut-off points to define it. Other investigations have preferentially used WHR, waist circumference and BMI, either together or separately 8,10,19,22,27,32 . On the one hand, WHR has been questioned due to the fact that the adipose tissue that builds up in the hips is variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation